Hubungan Perilaku Hidup Bersih Dan Sehat (PHBS) Dengan Pencegahan TB Paru Di Wilayah Kerja UPTD Puskesmas Lampahan Kecamatan Timang Gajah Kabupaten Bener Meriah - Afdalul Magfirah; Nurlaely HS (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2022)
TB is a contagious infectious disease that can attack various organs of the human body, especially the lungs (90%) because it is the most easily infected and transmits it to others. The ease of transmission by this bacterial infection, so it can interfere and become a scourge because it can cause death. The purpose of this study was to determine the relationship between clean and healthy living behavior (PHBS) and prevention of pulmonary TB in the working area of UPTD Puskesmas Lampahan, Timang Gajah District, Bener Meriah Regency. This research is analytical in nature, namely research with a cross sectional design. The population in this study was 5,573 families in the UPTD work area of the Lampahan Health Center, Timang Gajah District, Bener Meriah Regency. The sample in this study was 85 households using random sampling technique (random), data analysis using the chi-square test. The results showed that of the 85 respondents who applied Clean and Healthy Living Behavior (PHBS) by preventing pulmonary TB only 12 respondents (29.3%) and those who applied Clean and Healthy Life Behavior (PHBS) who did not do pulmonary TB prevention as many as 25 respondents (56.8%). Meanwhile, those who did not apply the existing Clean and Healthy Lifestyle (PHBS) to prevent pulmonary TB were 29 respondents (70.7%), and those who did not apply the Clean and Healthy Lifestyle (PHBS) with no prevention of pulmonary TB were only 19 respondents. (43.2%). The conclusion is that there is a relationship between Clean and Healthy Life Behavior (PHBS) and prevention of pulmonary TB, obtained p value = 0.019 (p < 0.05).